Application Status of Planktonic Algae in Evaluating the Freshwater Environment - YAN Ruyu; GAO Guiqing; YANG Junfei; FENG Yingying; JI Yong (Renmin Zhujiang)
In light of its indicating function in the freshwater environment,this paper introduces the applied research of planktonic algae in respects of indicating freshwater environment,monitoring and evaluating the eutrophication and heavy mental pollution of water body,elaborates the significance of establishing a biological monitoring system of planktonic algae on evaluating freshwater ecosystem,shows the problems in terms of physical habitat and ecological chain encountered in the monitoring and evaluating progress,discusses their influence on planktonic algae evaluation from the view of space hydrology,hydrodynamic force,aquatic vegetation,fishes,and algae,as well as proposes the future study of the related fields in hope to serve as the guideline of freshwater environment evaluation concerning planktonic algae in China.